The bidirectional relationship between severity of obsessive-compulsive symptoms and lifestyle factors in patients with obsessive-compulsive disorder: a contemporaneous and prospective analysis - du Mortier, Johanna A. M.; van Balkom, Anton J. L. M.; Twisk, Jos W. R.; van Oppen, Patricia; Visser, Henny A. D. (Frontiers in Psychiatry, 2025)
ObjectiveIn psychiatric disorders, lifestyle factors are known to influence both the development and course of the illness. However, little is known about the longitudinal relationship between lifestyle factors and OCD symptom severity, including the potential bidirectional, prospective association between them. This study examines both the contemporaneous and two-year prospective relationships between lifestyle factors and OCD symptom severity, as well as the reverse relationship—namely, the influence of OCD severity on lifestyle factors.MethodsLongitudinal data spanning six consecutive years were obtained from the Netherlands Obsessive Compulsive Disorder Association study (NOCDA). We examined the lifestyle factors: smoking, alcohol and illicit drug use, physical activity, and body mass index (BMI). Mixed models and Generalized Estimating Equations were employed to analyze the contemporaneous and bidirectional prospective relationships between these lifestyle factors and OCD severity.ResultsDrug and alcohol use, BMI, and physical activity did not exhibit a significant contemporaneous relationship with OCD severity. Smoking was significantly associated with more severe OCD symptoms: however depression influenced this relationship. Using alcohol was significantly associated with lower OCD severity. Among females, alcohol use was significantly associated with lower OCD severity two years later. Moderate and high levels of physical activity were significantly associated with lower OCD symptom severity two years later, whereas other lifestyle factors did not significantly predict future OCD symptom severity. OCD symptom severity did not predict any lifestyle factor, except among females, where higher OCD severity was associated with lower drug use two years later.ConclusionPrevious studies on other psychiatric disorders have found that unhealthy lifestyle factors are associated with more severe psychiatric symptoms. It appears that OCD might differ in these aspects. In the present study, drug and alcohol use, higher BMI, and a composite score of unhealthy lifestyle factors were not associated with more severe OCD symptoms and did not predict greater symptom severity two years later. However, consistent with findings in other psychiatric disorders, higher levels of physical activity were significantly associated with lower OCD symptom severity two years later. Further research is needed to determine whether increasing physical activity could result in less severe OCD symptoms.